Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Nilai Perusahaan pada Subsektor Makanan dan Minuman yang Terdaftar di BEI 2015-2018 - Anggun Wimidhati; Iin Indarti; Wenny Ana Adnanti (Jurnal Ilmiah Aset, 2021)
The purpose of this study was to analyze the effect of liquidity, leverage, and profitability on firm value of food and beverage companies listed on the Indonesia Stock Exchange period 2014-2018. The population were 72 and the sample were 40 companies. This study used the technique of classical assumption test and multiple linear regression analysis. Partial results of research showed that liquidity did not affect firm value, leverage had a significant positive effect on firm value, profitability had significant positive effect on firm value.